The darker side of travel: the theory and practice of dark tourism - Sharpley, Richard; Stone, Philip R (Aspects of tourism, 2009)
This book is a contemporary and comprehensive analysis of dark tourism. Drawing on existing literature, numerous examples and introducing new conceptual perspectives, it develops a theoretically informed foundation for examining the demand for and supply of dark tourism experiences.